2022
DOI: 10.5812/ijpr-127043
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Active Ionic Liquid-Assisted Cloud Point Extraction for Pre-Concentration and Determination of Cobalt Ions in Pharmaceutical Preparations

Abstract: : Herein we describe an efficient, simple, and precise micelle-mediated microextraction strategy based on the aggregation behavior of surface-active ionic liquids (SAILs) for the preconcentration and determination of cobalt ions in pharmaceutical preparations. Unlike the commonly used hydrophobic ionic liquids in IL-based microextraction methods, a water-soluble surface-active ionic liquid [1-hexadecyl 3-methylimidazolium chloride (C16MeImCl)] was used. A modified cloud point extraction (CPE) procedure based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…We identified limited data on neonatal adverse events following intravitreal anti-VEGF administration in pregnant women. Preclinical studies showed that intravitreal bevacizumab injections in rats resulted in adverse developmental effects when administered in early pregnancy, but not in the late stages of pregnancy [ 15 ]. None of the live births in our study were noted to have fetal malformations.…”
Section: Discussionmentioning
confidence: 99%
“…We identified limited data on neonatal adverse events following intravitreal anti-VEGF administration in pregnant women. Preclinical studies showed that intravitreal bevacizumab injections in rats resulted in adverse developmental effects when administered in early pregnancy, but not in the late stages of pregnancy [ 15 ]. None of the live births in our study were noted to have fetal malformations.…”
Section: Discussionmentioning
confidence: 99%